2012
DOI: 10.1007/978-1-4614-4989-8_27
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Oxygen Measurements and Personalized Medicine

Abstract: Tumor hypoxia is probably the most important not yet measurable factor that predicts the outcome of cancer therapy. Hypoxic tumors are resistant to radiation, chemotherapy, and surgery. They signal tumor cells to grow, invade, survive cytotoxic-factor assault, and increase metastatic activity. Therapies aimed at reversing hypoxia-related treatment resistance or normalizing hypoxia are proven effective with level 1 evidence. The weak link remains the lack of satisfactory methods of measurement of tumor oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For example, there is a dosemodifying factor of 2.5-3.0 between proliferating cells irradiated at < 2.5 mmHg and those irradiated at > 10 mmHg. Although 60 Gy of radiation is usually curative for tumor cell killing under normoxia, it would require > 150 Gy to reach the same killing for hypoxic cells (60 · 2.5 or 3) (163). In addition, in the absence of oxygen, decreased DNA DSBs are produced by free radicals after radiation therapy and/or the damaged products are repairable (73,164,216,231).…”
Section: Impact Of Tumor Hypoxia On Radiation Therapymentioning
confidence: 99%
“…For example, there is a dosemodifying factor of 2.5-3.0 between proliferating cells irradiated at < 2.5 mmHg and those irradiated at > 10 mmHg. Although 60 Gy of radiation is usually curative for tumor cell killing under normoxia, it would require > 150 Gy to reach the same killing for hypoxic cells (60 · 2.5 or 3) (163). In addition, in the absence of oxygen, decreased DNA DSBs are produced by free radicals after radiation therapy and/or the damaged products are repairable (73,164,216,231).…”
Section: Impact Of Tumor Hypoxia On Radiation Therapymentioning
confidence: 99%
“…Accumulated evidence suggested that HNSCC with sufficient oxygen supply has a better responsive rate to radiation in comparison with the hypoxic tumor [15, 16]. Furthermore, oxygen stress could trigger tumor cells to proliferate and allow them to undersurvive cytotoxic-factor assault [17]. …”
Section: Hypoxia Contributes To the Poor Therapeutic Outcome In Hnsccmentioning
confidence: 99%
“…Estimating oxygen levels in blood is of paramount importance in various preclinical and clinical applications, e.g., for the study of tumor characteristics, 1,2 personalized cancer treatment, [3][4][5][6] or the detection and monitoring of cerebral ischemia in newborns. 7,8 Quantitative optoacoustic (OA) imaging is an emerging technique that allows the determination of blood oxygen saturation (SO 2 ) by exploiting the distinct absorption spectra of oxy-and deoxyhemoglobin 9,10 while providing a higher spatial resolution in deep tissue than diffuse optical tomography.…”
Section: Introductionmentioning
confidence: 99%